Kinetics of the precipitation cation of nickel (II) - Юрченко, Ганна Олександрівна (Technology audit and production reserves, 2012)
The results of studies of the deposition process of nickel hydroxide (II) are given in the article. It is established that the completeness of precipitation of nickel ions (II) is only achieved when applying the method of pouring the reverse component (Ni2+ → OH-) at high pH values. The basic kinetic and thermodynamic parameters of the process is defined